Pengaruh pH Awal dan Suhu Penyimpanan terhadap Stabilitas Betasianin Ekstrak Pewarna dari Bunga Kenop (Gomphrena globosa L.) - Sugiastawa, I Made; Wartini, Ni Made; Arnata, I Wayan (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI, 2021)
Globe amaranth is a flower that can be used as a natural dye. The flower has a high betacyanin. This study aimed to determine the effect of initial pH and the temperature in stability extent of globe amaranth dye extract, with determined the initial pH and globe amaranth flower temperature with the maximum stability of dye extract during the retention. This experiment used a complete randomized design with two factors. The first factor was the initial pH that consist of pH 4, pH 5, and pH 6. The second factor was the storage temperature consist of temperature 4±1ºC and temperature 28±2ºC. The data were analyzed through analysis of variance in determined the effect of each factors. The results showed the initial pH had significant effect on betacyanin levels  and value of brightness level (L*), redness level (a*), and yellowish level (b*) during the storage  of globe amaranth dye extract. The temperature had significant effect on betacyanin levels  and the value of brightness level (L*), value of the level of redness (a*) on the third and fourth weeks, and a significant effect of yellowish (b*) only on the first and third weeks, a significant effect of yellowness (b*) on the fourth week. The interaction of two treatments had significant effect in every week on betacyanin levels  and the value of the brightness level (L*) on the first and second weeks, the value of the level of redness (a*) on the second week, and significant effect of the yellowish level (b*) on third and fourth weeks. The dye extract from the globe amaranth was stable at initial pH 4 with (4±1ºC) cold temperature during the storage. During the control retention of  globe amaranth dye extract within four weeks caused a decrease on betacyanin levels 34.76% ,  redness level value (a*) 61.85%, and  it was an increase of brightness level (L*) 70 ,91%, the value of yellowish level (b*) 67.21%. Keywords :  Globe amaranth extract, betacyanin, pH, temperature, stability.